2021
DOI: 10.3390/cells10113018
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of microRNAs in Human Adult Erythropoiesis

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs, which play an important role in various cellular and developmental processes. The study of miRNAs in erythropoiesis is crucial to uncover the cellular pathways that are modulated during the different stages of erythroid differentiation. Using erythroid cells derived from human CD34+ hematopoietic stem and progenitor cells (HSPCs)and small RNA sequencing, our study unravels the various miRNAs involved in critical cellular pathways in erythroid maturation. We analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 117 publications
1
10
0
Order By: Relevance
“…Two miR clusters including miR182-5p and miR-125a-5p, miR99b-5p and let-7e-5p respectively, simultaneously with single miRs, miR-486-5p and miR3529-3p, were significantly upregulated upon erythropoiesis induction in both UT+hemin/EPO and LRF-OE+hemin/EPO, indicating the cell commitment to the erythroid lineage. These results are in consistency with other reported data [48]. MiR-126-5p was a unique case with repressed expression during erythropoiesis induction of UT with hemin/EPO treatment (Supplementary table 3).…”
Section: Down-regulation Of Mirnas Expression Mediated By Lrfsupporting
confidence: 93%
“…Two miR clusters including miR182-5p and miR-125a-5p, miR99b-5p and let-7e-5p respectively, simultaneously with single miRs, miR-486-5p and miR3529-3p, were significantly upregulated upon erythropoiesis induction in both UT+hemin/EPO and LRF-OE+hemin/EPO, indicating the cell commitment to the erythroid lineage. These results are in consistency with other reported data [48]. MiR-126-5p was a unique case with repressed expression during erythropoiesis induction of UT with hemin/EPO treatment (Supplementary table 3).…”
Section: Down-regulation Of Mirnas Expression Mediated By Lrfsupporting
confidence: 93%
“…Interestingly, there are few descriptions of miR-12136 in literature. Recently, it was identified during erythropoiesis [ 62 ], in adipose-derived stem cells from old or diabetic patients [ 63 ], in the secretome of menstrual blood-derived MSC [ 64 ]. miR-12136 was also found to be downregulated in EVs from adipose-derived MSC from patients with metabolic syndrome [ 65 ] and was enriched in human vascular smooth muscle cells during replicative senescence [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…FoxO3 positively regulates antioxidant enzymes like catalase and glutathione peroxidase. CRISPR-Cas9-mediated mutagenesis of miR451 confirmed that miR451 is necessary for erythroid differentiation and expression of transferrin receptor 1, also known as CD71 [163]. The miR144 family is expressed together with miR451 and was similarly found to be necessary for erythroid differentiation and CD71 expression [163].…”
Section: Erythrocytes and Ribonucleic Acid (Rna)mentioning
confidence: 94%
“…Once in the cytoplasm, the miRNA is further processed by Dicer and bound to Argonaute2 forming the RNA-induced silencing (RISC) complex. Some of the miRNAs of the erythrocyte like miR-451, miR-144, and miR-486 are involved in erythropoiesis [163]. MiR-451 is also associated with malaria, and miR-144 is correlated with hypoxia at high altitudes [159].…”
Section: Erythrocytes and Ribonucleic Acid (Rna)mentioning
confidence: 99%
See 1 more Smart Citation